Manganese Removal From Synthetic Wastewater Using Pyrolyzed Chicken Feather Fiber (PCFF) - Ahamad Lazin, Nur Fajrina (Universiti Sains Malaysia, 2018)
The presence of heavy metal in wastewater pose to various negative impact on human health and environment. During the past decades, many attempt made to produce low cost adsorbent prior wastewater treatment for removing polluting ions such as calcium, zinc, magnesium, and manganese from industrial water systems. However, current activated carbon available are expensive but innovative effort and research now are moving forward towards the production of activated carbon with utilization of natural waste product such as chicken feather fiber. This alternative yet is a simple, low-cost, environmentally friendly for wastewater treatment. This study investigated the removal of heavy metal from synthetic wastewater using Pyrolyzed Chicken Feather Fiber (PCFF). PCFF act as an activated carbon derived from waste chicken feather produced from the two stage of pyrolysis method at 195°C for 5 hours and 400°C for 2 hours respectively.. The result obtained reveal that percentage removal of manganese in this study was 33.55% at pH 5 and 0.8g of adsorbent, higher than previous research with removal of 11.44% of manganese at pH of 5 and 1.5g of adsorbent. The activated carbon then are characterize by SEM/EDX and Raman Spectroscopy. SEM images showed that the surface of PCFF-1and PCFF-3 is rougher whereas the surface of PCFF-2 is smoother thus providing the larger surface area for the adsorption process. However, Raman analysis showed that produced activated carbon was unable to adsorb the pollutants due to the size of the pore presence in the activated carbon, unsuitability of activated carbon for the removal of selected heavy metal and due to surface charges.